The Advantage of Rumen Fluid Collection Technique Using Trocar in Animal Welfare - Tiven, Nafly Comilo (Indonesian Animal Sciences Society, 2012)
Trocar, a tool to remove the gas in livestock that have bloated stomach, has been modified for rumen fluid collection, as an alternative methods in animal welfare aspects. Rumen fluid collection with trocar modification can be made very easy, cheap and fast at the local sheep, both in vitro and in vivo. After the collection, the trocar does not leave permanent scars because scars on the rumen wall and skin will heal and return to normal. The animal relatively does not suffer from pain and stress; feed intake and body weight do not decrease drastically and animal can live normal. The rumen fluid sampling technique with trocar is better than fistulation in animal welfare aspect. Key words: Animal welfare, fistulation, trocar